Astronomical Analysis: Viral Video of the Sun Rising from the North in Jeneponto - Andi Muh. Akhyar; Fatmawati Fatmawati; Rahma Amir; Nur Amalia; Achmad Nasyori (IAIN Manado, 2021)
This study aims to conduct an astronomical analysis of the viral video of the Sunrise from the north on Thursday, June 17, 2021, in Jeneponto Regency, South Sulawesi, Indonesia. The video shows a man testifying to the Sun's position in the north and associating this phenomenon as one of the signs of the Day of Judgment. It attracts much attention to become a trending topic, both of social, national, and international media. This research is descriptive with a qualitative approach using library research methods and content analysis of location, calculations, and images. Primary data was obtained through the interview, while secondary data came from related articles and books. Data collection techniques used documentations and relevant data or theories to the research question. Furthermore, the collected data were analyzed inductively and comparatively. Location analysis was carried out using the Google Maps application, and it was found that the coordinates of MAN Binamu Jeneponto were at 5.67o South (S) and 119.73 East (E). Through calculation analysis, it is known that day the Sun rose in Jeneponto at 06.08 WITA with an azimuth of 66° 35' 23